Homogeneous batch micro‐crystallization of proteins from ammonium sulfate. Issue 2 (8th February 2021) - Stohrer, Claudia; Horrell, Sam; Meier, Susanne; Sans, Marta; von Stetten, David; Hough, Michael; Goldman, Adrian; Monteiro, Diana C. F.; Pearson, Arwen R.
Abstract : This work demonstrates how the precipitating properties of ammonium sulfate can be exploited to drive the transition from vapour‐diffusion conditions to large‐scale batch micro‐crystallization and how the specific ammonium sulfate concentration can further be used to fine‐tune microcrystal size and size distribution. Abstract : The emergence of X‐ray free‐electron lasers has led to the development of serial macromolecular crystallography techniques, making it possible to study smaller and more challenging crystal systems and to perform time‐resolved studies on fast time scales. For most of these studies the desired crystal size is limited to a few micrometres, and the generation of large amounts of nanocrystals or microcrystals of defined size has become a bottleneck for the wider implementation of these techniques. Despite this, methods to reliably generate microcrystals and fine‐tune their size have been poorly explored. Working with three different enzymes, l ‐aspartate α‐decarboxylase, copper nitrite reductase and copper amine oxidase, the precipitating properties of ammonium sulfate were exploited to quickly transition from known vapour‐diffusion conditions to reproducible, large‐scale batch crystallization, circumventing the tedious determination of phase diagrams. Furthermore, the specific ammonium sulfate concentration was used to fine‐tune the crystal size and size distribution. Ammonium sulfate is a common precipitant in protein crystallography, making these findings applicable to many crystallization systems to facilitate the production of large amounts of microcrystals for serial macromolecular crystallography experiments.